Réponses

  • Utilisateur Brainly
2013-12-28T18:48:17+01:00
F(x)=ax²+bx+c
=a(x+b/(2a))²-Δ/(4a)
si
Δ<0 on pose Δ=-d=i²d avec d>0

donc f(x)=
a[(x+b/(2a))²-(i²d)/(4a²)]
             =a[(x+b/(2a))²-(iVd/(2a))²]
             =a(x-(-b-iVd)/(2a))(x+(-b+iVd)/(2a))
             =a(x-(-b-iV(-Δ))/(2a))(x+(-b+iV(-Δ))/(2a))
            
2013-12-28T19:05:00+01:00
F(x)=ax²+bx+c
=a(x+b/(2a))²-Δ/(4a)
si 
Δ<0 on pose Δ=-d=i²d avec d>0

donc f(x)=
a[(x+b/(2a))²-(i²d)/(4a²)]
             =a[(x+b/(2a))²-(iVd/(2a))²]
             =a(x-(-b-iVd)/(2a))(x+(-b+iVd)/(2a))
             =a(x-(-b-iV(-Δ))/(2a))(x+(-b+iV(-Δ))/(2a))